Environmental Impact Analysis of a Landfill in Segobang Village, Banyuwangi - Harliwanti Prisilia; Dimas Aji Purnomo; Ratih Nurhayati (Universitas Islam Raden Rahmat, Malang, 2026)
One of the growing environmental problems in many places is waste management. Landfills that are not managed effectively can affect public health and the quality of the surrounding environment. The purpose of this study is to examine how the landfill in Segobang Village, Banyuwangi, impacts the environment. This study was conducted using qualitative descriptive approach and semi quantitative approach data were collected through documentation, interviews, and field observations. The results show that the landfill pollutes the air with unpleasant odors, contaminates the soil due to waste accumulation, and pollutes water through leachate. In addition, a decline in environmental comfort and the emergence of minor illnesses such as coughs and skin irritation are social effects experienced by the community. Among the primary causes of these environmental impacts are a poor waste management system, a lack of supporting facilities, and low public awareness regarding environmental hygiene. Therefore, proper waste management is necessary to reduce the impact of pollution through improved facilities, environmental monitoring, and community training.